TERM EXTENSION OF DRUG PATENTS IN RUSSIA (REVIEW OF LEGISLATION AMENDMENTS) - K. V. Osipov (Разработка и регистрация лекарственных средств, 2019)
The article describes the procedure of patent term extension to be granted on inventions relating to drugs and of granting a supplementary patent in view of recent amendments introduced in the Civil Code of the Russian Federation. Some advices are given on drafting patent applications on such inventions.